Willingness to Pay Analyse for Green Cosmetics Product in Malang City - Puspasari, Ernita Dian; Endayani, Fatmasari; Herditya, Alfin Achmad Fahmi; Indira, Okshanela (Jambura Science of Management, 2024)
Purpose: This research aims to determine the characteristics of green cosmetics consumers in the city of Malang. Additionally, it seeks to analyze the estimates and percentage changes in prices of green cosmetics products that consumers are willing to pay.Design/Methodology/Approarch: Descriptive analysis and the Contingent Valuation Method are employed in this research. The respondents consist of women in Malang who have used green cosmetics products. The total number of respondents for this study is 100.Findings: The characteristics of the respondents in this study are predominantly women aged 26 to 35, working in the private sector, with expenditures exceeding Rp. 6,000,000. Overall, the majority of respondents in this study are willing to pay more for green cosmetics products. They express no objection because the benefits of green cosmetics products are not only advantageous for users but also contribute to environmental sustainability. Green cosmetics products such as serum, facewash, and sunscreen are frequently used and preferred by consumers.